Sputum culture reversion in longer treatments with bedaquiline, delamanid, and repurposed drugs for drug-resistant tuberculosis - Kho, Sooyeon; Seung, Kwonjune J.; Huerga, Helena; Bastard, Mathieu; Khan, Palwasha Y.; Mitnick, Carole D.; Rich, Michael L.; Islam, Shirajul; Zhizhilashvili, Dali; Yeghiazaryan, Lusine; Nikolenko, Elena Nikolaevna; Zarli, Khin; et al. (Nature communications, 2024)
Sputum culture reversion after conversion is an indicator of tuberculosis (TB) treatment failure. We analyze data from the endTB multi-country prospective observational cohort (NCT03259269) to estimate the frequency (primary endpoint) among individuals receiving a longer (18-to-20 month) regimen for multidrug- or rifampicin-resistant (MDR/RR) TB who experienced culture conversion. We also conduct Cox proportional hazard regression analyses to identify factors associated with reversion, including comorbidities, previous treatment, cavitary disease at conversion, low body mass index (BMI) at conversion, time to conversion, and number of likely-effective drugs. Of 1,286 patients, 54 (4.2%) experienced reversion, a median of 173 days (97-306) after conversion. Cavitary disease, BMI < 18.5, hepatitis C, prior treatment with second-line drugs, and longer time to initial culture conversion were positively associated with reversion. Reversion was uncommon. Those with cavitary disease, low BMI, hepatitis C, prior treatment with second-line drugs, and in whom culture conversion is delayed may benefit from close monitoring following conversion. In patients with drug-resistant tuberculosis who receive treatment with new and repurposed drugs, indicators of advanced disease and delayed conversion were associated with an increased risk of reversion. These factors may be targets for close monitoring.